Inflation Risk? - Paul De Grauwe (Intereconomics)
Abstract Inflation is on the rise again in the industrialised world. This has led to fears of a sustained surge in inflation. This article argues that while such fears may make sense in the US, they do not in the eurozone, where the monetary-fiscal policy mix has been much less expansionary than in the US. The fear expressed by some that the monetary overhang from the large injections of liquidity through quantitative easing might lead to inflation in the eurozone does not stand up to scrutiny either. The conclusion offers some observations on the monetary operating procedures in the ECB. It argues that in the future, when interest rates rise again, the ECB risks transferring all (and even more) of its profits to the banking system. This article proposes a way to avoid this unacceptable outcome.